THE NEGOTIATION IN STUDENTS’ CASUAL CONVERSATION (Universitas Negeri Semarang, 2012)
Studi ini bertujuan untuk (a) menggambarkan cara tentang bagaimana untuk menopang percakapan siswa, (b) menggambarkan pattern dari negotiation, (c) menggambarkan implikasi pedagogis temuan. Penelitian ini merupakan qualitative research dengan pendekatan Systemic Functional Linguistics dalam menganalisa casual conversation. Instrumen yang digunakan ialah Eggins dan Slade’s Move Network System, bahan diambil dari 10 chat dalam I ntensive course group Universitas Sunan Muria Kudus. Hasil temuan menunjukan bahwa respon peserta ditemukan 37,1% dikategorikan sustain, 45,7% merespon move dan 17,1% rejoinder. Tiga paten dari negosiasi yaitu (1) paten dari splitting Moves relevancy (2) collaborative support (3) dan particular choice of moves closed conversation exchange. Implikasi pedagogis adalah emosi yang muncul dalam teks dengan rincian 64% fungsional dan 36% non-fungsional. Mayoritas peserta setuju untuk meningkatkan pengembangan paten dengan memberikan peserta treatment menggunakan materi dengan konjungsi dan statemen yang dapat diterima dan menggunakan question tag.The Negotiation in Students’ Casual Conversation: The Case of Muria Kudus University’s Intensive Course Group Chat in Facebook aims at a) describing the way how participants sustain their conversation, b) describing the negotiation pattern, c) describing the pedagogical implication of the findings. It is a qualitative research with Systemic Functional Linguistics approach on analyzing Casual Conversation. The instrument was the Eggins and Slade’s Move Network system. The corpus was 10 transcribed chats of Intensive Course Group Chat Muria Kudus University. The findings showed that 37.1% of the participants’ response was Sustain:Continuing Move, 45.7% was Responding Move, and 17.1% was Rejoinder Move. Participants therefore negotiated around what had been proposed by the initiator. Three Negotiation patterning were: (1) a pattern of splitting Moves relevancy (2) a pattern of collaborative support, (3) a pattern of particular choice of moves closed conversation exchange; particular others opened the channel of a conversation. The pedagogical implication was that Emoticons appeared in the text 64% functioned conventionally, while 36% functioned un-conventionally. The domination of Responding:Agree Move should be encouraged to the production of Developing and Rejoinder Move by treating the participants with some materials like expanding message using acceptable conjunction and Statement with question tagging.